An analysis method for the performance of compliant cylindrical intershaft gas film seal considering centrifugal expansion effect. (March 2022) - Hou, Guoqiang; Su, Hua; Chen, Guoding
A compliant cylindrical gas film seal has the potential to adapt to the complex operating conditions of a dual-rotor aeroengine, with radial runout and eccentricity, due to its special structural characteristics. To accurately investigate the seal performance of a compliant cylindrical gas film seal on dual-rotor shafts, an aeroelastic coupling method is proposed. This method analyzes the performance of a compliant cylindrical intershaft gas film seal by taking the centrifugal expansion effect into consideration. The seal performance under homodromy and counter-rotating conditions, with and without the centrifugal expansion effect, is calculated, and various performance parameters are compared and analyzed. Furthermore, the influence mechanism of the direction of rotation of the two rotors on seal performance is revealed. The results show that seal performance under homodromy condition is greater than under counter-rotating condition, and for an aeroengine under homodromy condition, it is advantageous to apply the compliant cylindrical intershaft gas film seal. The effect of centrifugal expansion (in large-diameter and high-speed rotors) and rotor eccentricity on the performance of a compliant cylindrical intershaft gas film seal, as well as the impact of inner and outer rotor speed on leakage rate, are analyzed and presented in this study. The proposed aeroelastic coupling method provides a promising guidance for the performance analysis of the compliant cylindrical gas film seal in single and dual- rotor systems.